Comparative evaluation of accuracy of implants placed with thermoplastic and three-dimensional-printed surgical guides: A randomized controlled trial - Firasat Husain; Vishakha Grover; Nandini Bhaskar; Ashish Jain (Wolters Kluwer Medknow Publications, 2024)
Background: The current study was planned to evaluate the accuracy of dental implant placement with two different types of surgical guides: Thermoplastic and three-dimensional (3D) printed. Materials and Methods: A total of 32 implants were placed in 20 healthy, partially dentate individuals with an isolated single missing tooth. The implant sites were randomly allocated into two treatment groups: Group A (thermoplastic implant surgical guide, n = 16 implants) and Group B (3D printed implant surgical guide, n = 16 implants). All the cases in both groups were digitally planned according to a defined protocol, and a comparison of the planned and actual implant positions was performed using the medical image analysis software. The differences in the outcome variables, i.e., angular deviation (AD), 3D error at the entry, 3D error at the apex (3D EA), vertical deviation (VD), and composite deviation, were statistically analyzed. Results: All the outcome variables showed improvements, but statistically significant improvement was shown by AD (P = 0.005), 3D EA (P = 0.01), and VD (P = 0.007). The mean and standard deviation (SD) for AD, (3D EA), and VD were 5.58° ±1.93°, 0.96 ± 0.32 mm, and 0.58 ± 0.36 mm, respectively, for group A. The mean and SD for AD, (3D EA), and VD were 3.94° ± 0.64°, 0.64 ± 0.35 mm, and 0.29 ± 0.13 mm, respectively, for group B (P < 0.05). Conclusion: Within the limits of the study, dental implants placed using 3D-printed surgical guides were positioned clinically with greater accuracy, and fewer deviations were observed from their presurgical planned positions as compared to the thermoplastic surgical guides.